Risk Factors of Coronary Artery Abnormalities and Resistance to Intravenous Immunoglobulin Plus Corticosteroid Therapy in Severe Kawasaki Disease: An Analysis of Post RAISE. Issue 2 (February 2021) - Miyata, Koichi; Miura, Masaru; Kaneko, Tetsuji; Morikawa, Yoshihiko; Sakakibara, Hiroshi; Matsushima, Takahiro; Misawa, Masahiro; Takahashi, Tsutomu; Nakazawa, Maki; Tsuchihashi, Takatoshi; Yamashita, Yukio; Obonai, Toshimasa; et al.
Abstract : Background: Coronary artery abnormalities (CAAs) still occur in patients with Kawasaki disease receiving intensified treatment with corticosteroids. We aimed to determine the risk factors of CAA development and resistance to intensified treatment in Post RAISE (Prospective Observational Study on Stratified Treatment With Immunoglobulin Plus Steroid Efficacy for Kawasaki Disease)—the largest prospective cohort of Kawasaki disease patients to date. Methods: In Post RAISE, 2648 consecutive patients with Kawasaki disease were enrolled. The present study analyzed 724 patients predicted to be intravenous immunoglobulin (IVIG) nonresponders (Kobayashi score ≥5) who received intensified treatment consisting of IVIG plus prednisolone. The association between the baseline characteristics and CAA at 1 month after disease onset was examined. The association between the baseline characteristics and treatment resistance was also investigated. Results: Maximum Z score at baseline ≥2.5 (odds ratio, 3.4 [95% CI, 1.5–7.8]), age at fever onset <1 year (odds ratio, 3.4 [95% CI, 1.6–7.4]), and nonresponsiveness to IVIG plus prednisolone treatment (odds ratio, 6.8 [95% CI, 3.3–14.0]) were independent predictors of CAA development. Nonresponsiveness to IVIG plus prednisolone was significantly associated with 8 baseline variables. Baseline total bilirubin (odds ratio, 1.4 [95% CI, 1.2–1.7]) was the only significant independent predictor other than the variables included in the Kobayashi score, enabling treatment resistance to be identified at diagnosis. The area under the ROC curve was 0.74 (95% CI, 0.69–0.79). At a cutoff point of 1.0, the sensitivity and specificity for predicting treatment resistance were 71% and 65%, respectively. Conclusions: In Post RAISE, younger age at fever onset, a larger maximum Z score at baseline, and nonresponsiveness to IVIG plus prednisolone were risk factors significantly associated with CAA development. Nonresponders were able to be identified at diagnosis based on the total bilirubin value. To prevent CAA, more intensified or adjunctive therapies using other agents, such as pulsed methylprednisolone, ciclosporin, infliximab, and Anakinra, should be considered for patients with these risk factors. Registration: URL: https://www.umin.ac.jp/ctr/ ; Unique identifier: UMIN000007133.